The fulfillment of the surah of the news from the manuscript of James Al-Tabyan in the interpretation of the Quran / Moin al-Din Muhammad Bin Abdul Rahman Al-IJI, who died in 906 Ah (Journal of the College of Basic Education, 2024)
The study investigates a surah of the Holy Qur’an from one of the manuscript interpretations. This interpretation was initially classified by its author under the title Jami’ al-Bayan fi Tafsir al-Qur’an when he was forty years old, and at this stage the book was brief in its first form, but within thirty-three years of its writing The first version added many footnotes to the book, then the author refined, revised, trimmed and corrected the book until it came out in the form it has now. Then the author changed the name to Jami’ al-Tibyan fi Tafsir al-Qur’an.